Diverging effects of nicotine on motor learning performance: Improvement in deprived smokers and attenuation in non-smokers. (November 2017) - Grundey, J.; Amu, R.; Batsikadze, G.; Paulus, W.; Nitsche, M.A.
Abstract: Nicotine modulates cognition and neuroplasticity in smokers and non-smokers. A possible mechanism for its effect on learning and memory performance is its impact on long-term potentiation (LTP) and long-term depression (LTD). As neuroplasticity is closely connected to learning processes, we aimed to explore the effect of nicotine in healthy, young smokers and non-smokers on performance of the serial reaction time task (SRTT), a sequential motor learning paradigm. 20 nicotine-deprived smokers and 20 non-smokers participated in the study and were exposed to nicotine or placebo medication. Deprived smokers under placebo medication displayed reduced performance in terms of reaction time and error rates compared to the non-smoking group. After application of nicotine, performance in smokers improved while it deteriorated in non-smokers. These results indicate a restituting effect of nicotine in smokers in terms of cognitive parameters. This sheds further light on the proposed mechanism of nicotine on learning processes, which might be linked to the addictive component of nicotine, the probability of relapse and thus needs also be addressed in cessation treatment. Highlights: Nicotine deprived smokers and non-smokers differ in terms of motor learning performance. Nicotine re-administration in deprived smokers leads to improved motor learning performance. Nicotine administration in non-smokers leads to deterioration of motor learning performance. The results in smokers speak for a restitutional effect in both LTP-like neuroplasticity and learning performance.